2015
DOI: 10.1111/jopy.12179
|View full text |Cite
|
Sign up to set email alerts
|

Personality Predicts Health Declines Through Stressful Life Events During Late Mid‐Life

Abstract: Personality predicts the occurrence of dependent stressful life events (SLE; i.e., events reliant, at least in part, on an individual's behavior). This process, termed stress generation, contributes to psychiatric outcomes, but its role in physical health is unknown. Data were included from 998 participants (aged 55–64) in the St. Louis Personality and Aging Network (SPAN) study. Assessments occurred every 6 months for 18 months. Neuroticism, impulsivity, and agreeableness were measured with the Revised NEO Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 63 publications
4
27
0
Order By: Relevance
“…From the perspective of physical health, dispositional negativity is associated with sleep problems (Hintsanen et al, 2014), metabolic syndrome (Phillips et al, 2010), elevated cholesterol levels (Hengartner, Kawohl, et al, 2016), and a wide variety of other physical diseases and subjective health complaints (e.g., coronary heart disease; Deary, Weiss, & Batty, 2010; Gale et al, 2016; Iacovino, Bogdan, & Oltmanns, 2016; Jokela, Pulkki-Raback, et al, 2014; Lahey, 2009; Mund & Neyer, in press ). Among nearly 7,000 older adults (mean age = 68.4 years) followed as part of the Health and Retirement study, a one standard-deviation increase in dispositional negativity prospectively increased the odds of being diagnosed with a heart condition by 24%, lung disease by 29%, and hypertension by 37% during the four-year follow-up period (Weston, Hill, & Jackson, 2015).…”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of physical health, dispositional negativity is associated with sleep problems (Hintsanen et al, 2014), metabolic syndrome (Phillips et al, 2010), elevated cholesterol levels (Hengartner, Kawohl, et al, 2016), and a wide variety of other physical diseases and subjective health complaints (e.g., coronary heart disease; Deary, Weiss, & Batty, 2010; Gale et al, 2016; Iacovino, Bogdan, & Oltmanns, 2016; Jokela, Pulkki-Raback, et al, 2014; Lahey, 2009; Mund & Neyer, in press ). Among nearly 7,000 older adults (mean age = 68.4 years) followed as part of the Health and Retirement study, a one standard-deviation increase in dispositional negativity prospectively increased the odds of being diagnosed with a heart condition by 24%, lung disease by 29%, and hypertension by 37% during the four-year follow-up period (Weston, Hill, & Jackson, 2015).…”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
“…Increased stressor exposure has been observed using subjective ratings and more objective experimenter ratings of stressor intensity (Gleason, Powers, & Oltmanns, 2012; Iacovino et al, 2016; Jeronimus et al, 2014). For example, data from the Virginia Twin Registry ( n > 7,000) indicates that dispositional negativity strongly predicts job loss, marital problems, and conflicts with family and co-workers, but is unrelated to random misfortunes (e.g., robbery; Kendler, Gardner, & Prescott, 2003).…”
Section: Trait-state Links Inferred From Self-report and Behaviormentioning
confidence: 99%
“…Thus, one theory is that they may be more likely to generate stressful life events (SLEs) (Hammen, 1991;Kendler, Gardner, & Prescott, 2005;Os, Park, & Jones, 2001), which in turn predicts depression in NEUROTICISM AND LATE LIFE DEPRESSION 6 later life (Kendler & Gardner, 2016;Kendler, Karkowski, & Prescott, 1999). This association may be especially salient with respect to dependent SLEs, which are partly or entirely attributable to the person's own behavior (e.g., being fired from a job), rather than independent SLEs which the result of factors not directly attributable to the person's own behavior (e.g., losing a job due to the company closing) (Iacovino et al, 2016). Still, it remains unclear whether there are indirect effects of neuroticism on depression through SLEs (dependent or otherwise), as the few studies that have tested this association yielded conflicting results (Kercher, Rapee, & Schniering, 2009;Ormel, Oldehinkel, & Brilman, 2001).…”
mentioning
confidence: 99%
“…Relatively little is known about the causal pathways that link neuroticism and mental health outcomes more generally (Ferguson, 2013;Iacovino, Bogdan, & Oltmanns, 2016), in part due to the challenges of measuring neuroticism simultaneously with mental health outcomes (Lahey, 2009;Ormel, Rosmalen, & Farmer, 2004). For instance, measures of personality tend overlap in content with measures of depression and other mental health outcomes, thus inflating estimates of their association (Spijker, Graaf, Oldehinkel, Nolen, & Ormel, 2007).…”
mentioning
confidence: 99%
“…While empirical findings regarding agreeableness and conscientiousness are more sparse (Hampson et al, 2016;Lüdtke et al, 2011;Vaidya, Gray, Haig, & Watson, 2002), both could theoretically be expected to be inversely associated with objective stress (agreeableness through positive social relations and conflict avoidance; conscientiousness through a well-structured, healthy, and productive lifestyle). It has previously been shown that personality indirectly predicts health problems and physiological dysregulation through stressful life events (Hampson et al, 2016;Iacovino, Bogdan, & Oltmanns, 2016), making personality relevant in studies of AL and objective stress as well.…”
mentioning
confidence: 99%